REASSESSING LEGAL RECOGNITION OF AI: HUMAN DIGNITY AND THE CHALLENGE OF AI AS A LEGAL SUBJECT IN INDONESIA - Disemadi, Hari Sutra; Sudirman, Lu (Masalah-Masalah Hukum, 2025)
The rapid development of artificial intelligence (AI) presents complex challenges in legal theory, particularly regarding the question of AI as a legal subject. As AI becomes increasingly capable of creative work and decision-making, the question arises whether it should be recognized legally as an entity in its own right. This study explores the legal implications of recognizing AI as a legal subject through the lens of Immanuel Kant's philosophy, particularly focusing on human dignity. Kant argues that human dignity is intrinsic, grounded in the capacity for rational thought and moral responsibility, a characteristic AI lacks. Thus, recognizing AI as a legal subject risks undermining human dignity by equating human beings with entities that do not possess autonomy or ethical awareness. The study examines the current legal framework in Indonesia, highlighting the lack of clear regulation for AI, and explores the philosophical, ethical, and practical considerations involved in the legal treatment of AI. It argues that AI should be treated as a tool, not a legal subject, ensuring that human dignity remains the cornerstone of the legal system. The paper concludes by advocating for a fragmented, sector-specific approach to AI regulation in Indonesia, ensuring more focused oversight while protecting human dignity.